Conceptual Correspondence Monitoring: Multimode Information Logistics Approach - Peteris Rudzajs; Marite Kirikova (Complex Systems Informatics and Modeling Quarterly)
The paper addresses the problems arising in situations where conceptual correspondence has to be monitored, i.e., there are two or more structures of concepts which have a physical or abstract mapping and the changes in the structures of concepts may introduce the changes in the mapping. Usually the monitoring of conceptual correspondence requires manual, semi-automatic, and automatic information processing and exposes high level of complexity. The integration of different types of information processing units can be achieved by the use of multimode information logistics. The paper discusses challenges of the use of multimode information logistics in monitoring conceptual correspondence and proposes an approach that helps to partly meet the discussed challenges by jointly using functional and morphological spaces of representation of information logistics networks. The proposed approach is illustrated by an example of monitoring conceptual correspondence between knowledge demand and offer in the area of education.